Mean Length of Finite Clusters in Directed Compact Percolation Near a Damp Wall - Essam, J.; Lonsdale, Heather; Owczarek, A. (2011)
The mean length of finite clusters is derived exactly for the case of directed compact percolation near a damp wall. We find that the result involves elliptic integrals and exhibits similar critical behaviour to the dry wall case. © 2011 Springer Science+Business Media, LLC.